Aplikasi Quality Function Deployment Untuk Redesign Kontainer Penyimpanan Pada Industri Kemasan Kaleng - Debrina Puspita Andriani; Mochamad Choiri; Dea Priharseno (Jurnal Teknik Industri, 2017)
The manufacturing industry which produces cans with non-food industrial markets are conducting an assessment for the storage activity of canned product that have been using containers in their warehouse. This is due to the fluctuation of product demand in the diameter of 57 mm that exceeds the warehouse capacity in some periods, thus causing pounding in the pound area and not optimally charging the component due to the many types of containers used in the warehouse area of the component.  In this research, the re-designing of container using Quality Function Deployment method had done to overcome these problem. After obtaining the proposal results of container design, then redesigned the layout in the pounding area. Based on the analysis results, the volume capacity of the container proposal on pounding area was larger 69.120.000.000 mm3 compared to the existing containers, thus the container proposal can be filled more optimal with the can components than the existing containers.